Chemical constituents produced by the marine fungi Penicillium sp. M839 and their antimicrobial evaluation - Tran, Van Hieu; Vu, Van Nam; Nguyen, Thuy Linh; Le, Thi Hong Minh; Doan, Thi Mai Huong; Pham, Van Cuong (Vietnam Journal of Marine Science and Technology, 2025)
From the agar-based culture of the marine-derived Penicillium sp. M839 strain, nine known compounds were isolated and structurally determined, including fumiquinazoline D (1), fumiquinazoline B (2), cerevisterol (3), stoloniferol B (4), norhaman (5), 3,4-dihydroxy-6,7-dimethyl-quinolin-2-carboxylic (6), uracil (7), 3-methyl uracil (8), thymine (9). These compounds were characterized via 1D and 2D NMR spectroscopic and mass spectrometric analyses. Compounds 2 and 8 were first recognized from the genus Penicillium, while the remaining compounds were previously isolated from this genus. Compounds 1–6 were evaluated for their antimicrobial activity against a panel of test microorganisms (three Gram-positive bacteria: Enterococcus faecalis, Staphylococcus aureus, Bacillus cereus; three Gram-negative bacteria: Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica and one yeast strain Candida albicans). The results showed that compound 6 displayed strong antimicrobial activity against two Gram-negative bacteria E. coli and S. enterica, with the MIC values of 32 and 64 µg/mL, respectively. In addition, the remaining compounds 1–5 inhibited against all test microorganisms with MIC values ranging from 64 to 256 µg/mL.